Interstitial high-dose-rate brachytherapy as a boost in synchronous prostate and rectal cancer treatment: case report and literature review - Konat-Bąska, Katarzyna (J Contemp Brachytherapy, 2020)
PURPOSE: Prostate and colorectal cancers are the first and the third most popular malignancies in male population, in which some patients may develop these tumors metachronously or synchronously. At present, there are no standard recommendations, and oncologists need to provide an optimal management for two different cancers with an acceptable risk of possible treatment of adverse effects. MATERIAL AND METHODS: This case report presents the treatment of a 61-year-old patient suffering from synchronous prostate and rectal cancer. Both malignancies were locally advanced, histologically proven, and defined as cT2cN0M0 stage prostate and cT3N2M0 stage rectal adenocarcinoma. RESULTS: Multidisciplinary treatment team decided on synchronous radical treatment of both malignancies. The patient was qualified to long-term androgen deprivation therapy (ADT) and preoperative chemoradiation, with a total dose of 50.4 Gy in 28 fractions delivered with intensity modulated radiation therapy/image-guided radiation therapy (IMRT/IGRT) to a proper prostatic and rectal gross and nodal clinical target volume (CTV) with concurrent 5-fluorouracil. Additional dose of 15 Gy in a single fraction was delivered to prostate with interstitial HDR brachytherapy within a week after external beam radiotherapy (EBRT). After 8 weeks, the patient underwent sphincter-sparing surgery, with total mesorectal excision. Treatment tolerance was good, and genitourinary toxicity was not observed until now. At present, the patient is 45 months after completion of chemoradiation and surgery. Current prostate specific antigen (PSA) level is < 0.003 ng/ml, with no evidence of locoregional recurrence or distant metastases. Patient completed long-term ADT. CONCLUSIONS: High-dose-rate (HDR) brachytherapy as a boost seems to be well-tolerated and effective option for delivering proper treatment dose to prostate in case of simultaneous treatment of rectal and prostate cancer.